Revision of the New World genus Peckia Robineau-Desvoidy (Diptera: Sarcophagidae) - Buenaventura, Eliana; Pape, Thomas (Zootaxa, 2013)
The New Worldand largely Neotropical genus Peckia Robineau-Desvoidy, 1830 is revised with a key to all species. Peckia is considered a senior synonym of Guanoxipha Lehrer, 2012, n. syn. and of Sarcodexia Townsend, 1892, n. syn., the first one under Squamatodes Curran and the latter maintained as a valid subgenus, which here is redefined giving the new generic combinations Peckia (Sarcodexia) lambens (Wiedemann, 1830), n. comb. and P. (S.) notata (Lopes, 1935), n. comb.; and the new subgeneric affiliations P. (S.) aequata (Wulp, 1895), P. (S.) chirotheca (Hall, 1933), P. (S.) dominicana (Lopes, 1982), P. (S.) florencioi (Prado & Fonseca, 1932), P. (S.) roppai (Lopes & Tibana, 1982) and P. (S.) tridentata (Hall, 1937). Peckia virgo (Pape, 1994) is transferred from subgenus Euboettcheria Townsend, 1927 to subgenus Squamatodes Curran, 1927. Sarcophaga adolenda Lopes, 1935 is transferred from its current position in Peckia to the genus Retrocitomyia Lopes, 1982, n. comb. A total of 67 species are recognized and grouped in the subgenera Euboettcheria, Pattonella Enderlein, 1928, Peckia Robineau-Desvoidy, 1830 (sensu stricto), Sarcodexia and Squamatodes. Nine new species are described, viz., Peckia (Euboettcheria) santamariae n. sp. (Colombia), Peckia (Euboettcheria) cacao n. sp. (Costa Rica), Peckia (Euboettcheria) calixtoi n. sp. (Puerto Rico), Peckia (Euboettcheria) hernandosi n. sp. (Ecuador), Peckia (Pattonella) kladosoides n. sp. (Colombia), Peckia (Peckia) cocopex n. sp. (Costa Rica: Cocos Island), Peckia (Peckia) sarmientoi n. sp. (Ecuador), Peckia (Peckia) rosalbae n. sp. (Colombia) and Peckia (Sarcodexia) cocos n. sp. (Costa Rica: Cocos Island). The following new synonymies are proposed as junior synonyms under their respective species: under Peckia (Euboettcheria) tridentata (Hall, 1937) is Euboettcheria alvarengai Lopes & Tibana, 1982, n. syn.; under Peckia (Peckia) chrysostoma (Wiedemann, 1830) is Paraphrissopoda hugolopesiana Lehrer, 2006, n. syn.; under Peckia (Peckia) pexata (Wulp, 1895) are Sarcophaga concinnata Williston, 1896, n. syn., Sarcophaga otiosa Williston, 1896, n. syn. and Paraphrissopoda catiae Lehrer, 2006, n. syn.; under Peckia (Peckia) rubella (Wiedemann, 1830) is Sarcophaga capitata Aldrich, 1916, n. syn. and under Peckia (Squamatodes) trivittata (Curran, 1927) is Squamatodes stahli Dodge, 1966, n. syn. Lectotypes are designated for Sarcophaga aequata Wulp, 1895, Sarcophaga concinnata Williston, 1896, Sarcophaga otiosa Williston, 1896 and Sarcophaga volucris Wulp, 1895. Paraphrissopoda alvesia Lehrer, 2006 is deemed an unavailable name as no depository was given for the putative type material.